Profitability, Leverage and Liquidity Analysis on Share Prices In Banking Companies on the Indonesia Stock Exchange - Framita Framita; Viola Syukrina E Janrosl (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
This work aims to provide consideration in investing in banking companies listed on the Indonesia Stock Exchange by examining the effect of profitability, leverage and liquidity variables on stock prices. Purposive sampling is a technique to determine the sample used in this work. In which the population is 45 banking sector companies and the sample obtained is 19 banking companies listed on the Indonesia Stock Exchange for the observation period from 2017-2021. This work uses secondary data in the form of an annual report on the banking sector from the annual report published on the official website of the Indonesia Stock Exchange or from the official website of each agency. The data analysis technique uses multiple linear regression analysis and software SPSS version 25 as a medium for testing hypotheses. The results of this study prove that Profitability (Return on Equity) has a significant effect on stock prices, while Leverage (Debt to Equity Ratio) and Liquidity (Current Ratio) have no significant effect on stock prices. Profitability (Return on Equity), Leverage (Debt to Equity Ratio) and Liquidity (Current Ratio) simultaneously have a significant effect on stock prices of banking companies listed on the Indonesia Stock Exchange.